MIGA 2007 Annual Report - Multilateral Investment Guarantee Agency (Washington, DC: World Bank, 2012)
In this report several records stand out from fiscal year 2007: Nearly half (48 percent) of projects supported by MIGA were in IDA-eligible countries, bringing MIGA's outstanding exposure in IDA countries to 41 percent. In addition, 38 percent of the projects supported during the year were in Africa, where MIGA has supported critical investments with a total of $2.3 billion in guarantees since 1991. The 2007 review also illustrates MIGA's commitment to supporting developing country investors, which represent a growing source of foreign direct investment in the developing world. These achievements point to the institution's strong dedication to confronting poverty-especially where it is most dire. Fiscal 2007 was also a strong year for MIGA's non-guarantee activities, with 44 technical assistance projects conducted in 29 countries in all regions, in addition to several regional and global initiatives. The fiscal year also registered important innovations in MIGA's delivery of investment-related information, with the launch of two new knowledge websites on foreign investment and political risk insurance. The report stresses that MIGA not only needs to adapt to a changing world: it must find a way to support the inclusive and sustainable globalization that will help all countries, particularly the poorest, to take advantage of ongoing changes and opportunities in the world economy.